Long-Term Time in Target Range for Systolic Blood Pressure Since Childhood and Midlife Arterial Stiffness - Yang Wang, MD, PhD; Han Qi, PhD; Hao Jia, MD; Dan Wang, MD; Yue Sun, MD; Bo-Wen Zhang, MPH; Ming-Fei Du, MD; Gui-Lin Hu, MD; Zi-Yue Man, MD; Chao Chu, MD, PhD; Xiao-Jun Yang, MPH; Teng Zhang, MD; et al. (JACC: Asia)
Background: Elevated blood pressure (BP) in childhood is associated with adult hypertension and arterial stiffness. However, the effect of long-term time in target range (TTR) for BP since childhood on the risk of arterial stiffness in midlife remains unclear. Objectives: The purpose of this study was to determine the independent association of TTR for systolic blood pressure (SBP) from childhood to midlife with arterial stiffness in adulthood. Methods: This study used data from the ongoing cohort of the Hanzhong Adolescent Hypertension Study. SBP-TTR was assessed over 36 years, with the target ranges of SBP defined as the 90th to 95th percentile of SBP for age, sex, and height in childhood, and 110 to 130 mm Hg in adulthood. Arterial stiffness was defined as brachial-ankle pulse wave velocity >1,400 cm/s. Results: Of the total 1,959 participants, 55.5% (1,088 of 1,959) were men, and the mean age was 49 years. The risk of arterial stiffness exhibited a gradual decrease with increasing SBP-TTR over the 36-year follow-up. Compared with the participants in the lowest quartile of SBP-TTR from childhood to midlife, those in the highest quartile showed significantly reduced arterial stiffness risk in midlife. This association persisted even after adjusting for mean SBP and SBP variability. Furthermore, men in the highest quartile of SBP-TTR demonstrated a markedly lower arterial stiffness risk than those in the lowest quartile, whereas this effect was not observed in women. Conclusions: Higher long-term SBP-TTR from childhood to midlife is associated with a reduced risk of arterial stiffness in midlife, regardless of the mean SBP or SBP variability.